Ricci Solitons on CR-Submanifolds of Maximal CR Dimension of a Complex Space Form (Global Journal of Science Frontier Research, 2017)
Abstract not found
Keywords: Ricci soliton; complex space form; CR-submanifolds of maximal CR dimension